2017
DOI: 10.1038/cddis.2016.352
|View full text |Cite|
|
Sign up to set email alerts
|

MCM7 promotes cancer progression through cyclin D1-dependent signaling and serves as a prognostic marker for patients with hepatocellular carcinoma

Abstract: DNA replication is a central procedure of cell proliferation, whereas aberrant DNA replication is indicated to be a driving force of oncogenesis. Minichromosome maintenance complex component 7 (MCM7) plays an essential role in initiating DNA replication. To investigate the potential oncogenic properties and prognostic value of MCM7 in hepatocellular carcinoma (HCC), we conducted immunohistochemistry staining of MCM7 in 153 HCC samples and found that MCM7 high expression level was associated with worse overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 41 publications
4
71
0
Order By: Relevance
“…Its sensitivity for HCC screening ranges from 41 to 65% at a cutoff of 20 ng/mL [53][54][55][56]. In recent years, various biomarkers have emerged for diagnosing HCC and predicting patient outcome, including glypican 3 and insulin-like growth factor (IGF)II mRNA [57], Keap1 and pNrf2 [58], 3-microRNA and AFP [59], CXCL1 [60], minichromosome maintenance complex -7 [61], and IGF1 receptor [62], among others.…”
Section: Discussionmentioning
confidence: 99%
“…Its sensitivity for HCC screening ranges from 41 to 65% at a cutoff of 20 ng/mL [53][54][55][56]. In recent years, various biomarkers have emerged for diagnosing HCC and predicting patient outcome, including glypican 3 and insulin-like growth factor (IGF)II mRNA [57], Keap1 and pNrf2 [58], 3-microRNA and AFP [59], CXCL1 [60], minichromosome maintenance complex -7 [61], and IGF1 receptor [62], among others.…”
Section: Discussionmentioning
confidence: 99%
“…Through this mechanism, MCM7 initiates DNA replication, which is a key process in cell cycle progression. (Qu et al 2017) CKS2 is activated by the Wnt/βcatenin signaling pathway and promotes cell proliferation and inhibits apoptosis, which makes the HCC cells more aggressive as its overexpression is more frequently observed in poorly differentiated tumors. (Li et al 2018;Shen et al 2010) KIF23 depletion inhibits tumor formation by inducing apoptosis in certain types of cancer, such as lung adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…DNA replication is a central process in cell proliferation, while aberrant DNA replication is a driving force of oncogenesis. It has been reported that overexpressed MCM7 is associated with a poor prognosis of HCC patients, and MCM7 promotes HCC cell proliferation via upregulating MAPK-cyclin D1 pathway both in vitro and in vivo 32 . In addition, the hallmark MYC targets proteins, and the cell cycle checkpoint proteins involved in G2/M transitions, are also among the upregulated protein networks.…”
Section: Differentially Regulated Proteins Characterized In the Hcc Cmentioning
confidence: 99%